UTILIZATION OF EDTECH PLATFORMS IN IMPROVING ACADEMIC RESPONSIBILITY OF ELEMENTARY SCHOOL STUDENTS - Ahmad, Rohmanuddin; Adi Wibawa, Gandung; Erna Yayuk (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study discusses the issue of low academic responsibility among elementary school students in managing the learning process in the digital age. The research subjects consisted of 12 fifth-grade students at SD Negeri 4 Jatigunung, a classroom teacher, and three parents. Using a qualitative case study approach, data were obtained through observation, interviews, and documentation. Furthermore, the data were analyzed using Miles and Huberman's interactive model, which includes the stages of data reduction, presentation, and verification. The purpose of this study is to analyze the use of Educational Technology (EdTech) platforms such as Ruang Murid, Google Classroom, Canva Edu, and Quizizz in improving student discipline, independence, and learning time management. The results of the study show that the use of EdTech has a positive effect on students' academic behavior, characterized by increased punctuality of assignment collection, active participation, and self-reflection skills. However, digital distractions and inequality of access to technology are still the main obstacles. This study concludes that EdTech integration plays an effective role as digital scaffolding in shaping academic responsibility, especially when balanced with character education, teacher mentoring, and parental involvement in a collaborative digital learning ecosystem.